2018
DOI: 10.1029/2017jd028172
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Synoptic Weather Patterns and their Persistency on Free Tropospheric Carbon Monoxide Concentrations and Outflow in Eastern China

Abstract: The relationship between synoptic weather patterns (SWPs) and variability of air pollution has not been fully understood. In this study, we assess the sensitivity of carbon monoxide (CO) concentrations and outflow in the free troposphere over eastern China to SWPs and their persistency, using daily CO data from the spaceborne Atmospheric Infrared Sounder (AIRS) instrument from 2003 to 2015. The SWPs over eastern China are classified into eight patterns following the Kirchhofer approach. On a regional average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 88 publications
(155 reference statements)
0
27
0
Order By: Relevance
“…In this section, we compare the trend in CO total column over Asia and the trend in biomass burning, to explore a linkage between the two. Since CO emitted from biomass burning can be transported across continents [56][57][58], the trends in biomass burning both inside and outside Asia are examined.…”
Section: Comparison Of the Trend In Atmospheric Carbon Monoxide With mentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we compare the trend in CO total column over Asia and the trend in biomass burning, to explore a linkage between the two. Since CO emitted from biomass burning can be transported across continents [56][57][58], the trends in biomass burning both inside and outside Asia are examined.…”
Section: Comparison Of the Trend In Atmospheric Carbon Monoxide With mentioning
confidence: 99%
“…Zheng et al [24] stated that CO from chemical production, as well as from oceanic and biogenic sources changes a little on a global scale. In contrast, atmospheric transport play a confounding role in modulating the CO trends in a receptor region [5,34,56]. Zheng et al [24] identified a declining trend in the global CO budget in 2000-2017, driven by reduced anthropogenic emissions in the US, Europe, and China, as well as by reduced biomass burning emissions globally.…”
Section: Impacts Of Biomass Burning On the Interannual Variation And mentioning
confidence: 99%
See 1 more Smart Citation
“…Weather classification is a well-established tool to characterize atmospheric processes at multiple scales and further to study air pollution-weather relationship (Han et al, 2018b). The methods for weather classification can be generally categorized into three groups: subjective, mixed, and objective, depending on the automatic degree during the classification process (Huth et al, 2008 can also be categorized in more detail according to the basic features of each classification algorithm (Philipp et al, 2014).…”
Section: Classification Of the Synoptic Weather Patternsmentioning
confidence: 99%
“…Third, we examine the sensitivity of daily surface ozone to the variation in synoptic weather systems. Considering the complexity of the synoptic meteorology in eastern China (Ding et al, 2017;Han et al, 2018b), we employ an objective clustering technique, the self-organizing map (SOM), to identify the predominant synoptic weather patterns (SWPs). In the following sections, we introduce the data and methods in section 2.…”
Section: Introductionmentioning
confidence: 99%